2008
DOI: 10.1055/s-2007-1024199
|View full text |Cite
|
Sign up to set email alerts
|

Endosonographisch geführte transgastrale Drainage von Pankreaspseudozysten

Abstract: Endoscopic ultrasound-guided transgastric drainage of a pancreatic pseudocyst is an effective treatment with few complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Several studies have reported morbidity and mortality in the range of 0% to 4%, but common characteristic of all the above is the small number of the patients included, ranging from 11 to 36. 15,[19][20][21] Varadarajulu and colleagues in 2008 performed a randomized trial to compare surgical versus endoscopic cyst-gastrostomy. In this trial, the number of patients in the endoscopic arm was 20 and the morbidity and mortality was reported as 0%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported morbidity and mortality in the range of 0% to 4%, but common characteristic of all the above is the small number of the patients included, ranging from 11 to 36. 15,[19][20][21] Varadarajulu and colleagues in 2008 performed a randomized trial to compare surgical versus endoscopic cyst-gastrostomy. In this trial, the number of patients in the endoscopic arm was 20 and the morbidity and mortality was reported as 0%.…”
Section: Discussionmentioning
confidence: 99%
“…These data show clearly that, although endoscopic drainage could be highly effective, the actual success rate was dependent on the type of fluid collection. In the management of PC very high success rates of more than 91% 9,15,25,29,35,37 and even up to 100% 13,26,40 were achieved. In particular, the use of EUS was also clearly superior to non‐EUS guided transmural drainage because EUS allowed non‐bulging PC to be drained.…”
Section: Discussionmentioning
confidence: 99%
“…EUS has been shown to change the management strategy in 37.5% of cases referred for endoscopic drainage 9 . We reviewed the results of larger case series of endoscopic drainage that were published up to December 2008 and summarized the data in Table 2 2,6,10–40 …”
Section: Discussionmentioning
confidence: 99%
“…Wiersema [14] published the first case of pseudocyst drainage entirely guided by endosonography without the utilization of fluoroscopy. Subsequent series utilizing this method have reported good success rates and safety profiles [15][16][17] . Free perforation during EUS-guided drainage of pancreatic pseudocysts is a rare complication which is estimated to occur at a rate of 1% [18,19] .…”
Section: Discussionmentioning
confidence: 99%